Effect of glycerol and sodium chloride on the shelf-life of fresh noodle - Norazlin, Supandi (2016)
Fresh noodles are wheat flour product that become staple food in Malaysian cuisine. The world consumption of noodle product has increase in recent years due to the ease of transportation, and cooking purposes. Nevertheless, the fresh noodle is easily perishable due to the high water content and improper storage condition. Most of the chemical preservatives used in fresh noodle nowadays are linked to several problem such as digestive problems, cancer, neurological conditions, attention deficit hyperactivity disorder, heart disease, and obesity. Thus, the objective of this study is to investigate the effects of sodium chloride and glycerol to the shelf-life extension of fresh noodles. The microbial growth, pH, moisture content and sensory attributes are the process parameters evaluated during the days of storage time at the room temperature. Glycerol was added to decrease the water activity content of the noodles. In addition, salt was also used in this experiment to inhibit the enzyme activities and the growth of microorganisms in fresh noodles, thus extending their shelf life. The sensory attributes such as odour, colour, viscoelasticity, and texture were used as the characteristics evaluated using quantitative descriptive analysis (QDA). Integral scores were given from 1 to 25 in which 25, denotes as excellent quality and 1 as completely deteriorated quality. The data obtained were expressed as the mean and standard deviation from three replicates and were analysed using SPSS software version 23. There are two modified sample used in this studied with the addition of glycerol (GL) and sodium chloride (S) as additive according to ratio of GL:S 2:4 for sample A and 4:2 for sample B. Initial TPC for both sample A and B were log 5 CFU/mL and significantly increased to log 7 CFU/mL at the end of the storage period for 7 days. Linear regression analysis between storage time and pH for sample B showed the strongest correlation (R2 = 0.959 and p = <0.001). The correlation between storage time and moisture content for sample A demonstrated strong correlation (R2= 0.956 and p = <0.001). The high composition of glycerol in sample B give the best result for all the process parameters studied.